2015
DOI: 10.1103/physrevlett.114.251603
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Quantum Time Crystals

Abstract: In analogy with crystalline solids around us, Wilczek recently proposed the idea of "time crystals" as phases that spontaneously break the continuous time translation into a discrete subgroup. The proposal stimulated further studies and vigorous debates whether it can be realized in a physical system. However, a precise definition of the time crystal is needed to resolve the issue. Here we first present a definition of time crystals based on the time-dependent correlation functions of the order parameter. We t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
459
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(482 citation statements)
references
References 24 publications
(31 reference statements)
13
459
3
1
Order By: Relevance
“…Subsequent work developed more precise definitions of such time translation symmetry breaking (TTSB) [6][7][8] and ultimately led to a proof of the "absence of (equilibrium) quantum time crystals" [9]. However, this proof leaves the door open to TTSB in an intrinsically out-of-equilibrium setting, and pioneering recent work [10,11] has demonstrated that quantum systems subject to periodic driving can indeed exhibit discrete TTSB [10][11][12][13]; such systems develop persistent macroscopic oscillations at an integer multiple of the driving period, manifesting in a sub-harmonic response for physical observables.…”
mentioning
confidence: 99%
“…Subsequent work developed more precise definitions of such time translation symmetry breaking (TTSB) [6][7][8] and ultimately led to a proof of the "absence of (equilibrium) quantum time crystals" [9]. However, this proof leaves the door open to TTSB in an intrinsically out-of-equilibrium setting, and pioneering recent work [10,11] has demonstrated that quantum systems subject to periodic driving can indeed exhibit discrete TTSB [10][11][12][13]; such systems develop persistent macroscopic oscillations at an integer multiple of the driving period, manifesting in a sub-harmonic response for physical observables.…”
mentioning
confidence: 99%
“…This notion of time crystal is close in spirit to the attempted definition in Ref. 23, where a no-go theorem was proved concerning spontaneous breaking of continuous time translation symmetry. This no-go theorem is inapplicable to the present systems for a number of reasons, in particular our Hamiltonians explicitly break continuous time evolution symmetry.…”
Section: Structure Of the Floquet Spectrum And Time Crystalsmentioning
confidence: 94%
“…The proposal of such a "time crystal" 2 for time-independent Hamiltonians has led to much discussion, with the conclusion that such structures cannot exist in the ground state or any thermal equilibrium state of a quantum mechanical system [4][5][6] . A simple intuitive explanation is that quantum equilibrium states have time-independent observables by Time (100 Floquet periods) construction; thus, time translation symmetry can only be spontaneously broken in non-equilibrium systems [7][8][9][10] .…”
mentioning
confidence: 99%